Composition of forage and grain from genetically modified DP202216 maize is equivalent to non-modified conventional maize (Zea mays L.). Issue 2 (3rd April 2019) - Anderson, Jennifer A.; Hong, Bonnie; Moellring, Emily; TeRonde, Sarah; Walker, Carl; Wang, Yiwei; Maxwell, Carl
ABSTRACT: DP202216 maize was genetically modified to increase and extend the expression of the zmm28 gene relative to native zmm28 gene expression, resulting in plants with enhanced grain yield potential. Standard nutritional and compositional parameters for maize grain and forage (e.g., proximates, fiber, minerals, amino acids, fatty acids, vitamins, anti-nutrients, secondary metabolites) from DP202216 maize were compared to grain and forage from non-modified near-isoline maize (control). Three amino acids (glycine, methionine, and serine) and two vitamins (vitamin B1 and vitamin B3) were statistically different between DP202216 and control maize grain but were not statistically different when adjusted using the false discovery rate method. These analyte values also fell within the ranges of natural variation of non-modified commercial maize varieties supporting that statistical differences were not biologically relevant. The composition of grain and forage from DP202216 maize is comparable to grain and forage from non-modified maize with a history of safe use.